2003
DOI: 10.1556/comec.4.2003.2.1
|View full text |Cite
|
Sign up to set email alerts
|

A partial order approach for summarizing landscape quality

Abstract: We propose a simple mathematical framework to define consistently the environmental quality of a given landscape based on the relative abundances of the constituting land cover classes. Unlike traditional diversity measures, the new method does not evaluate the simple dispersion of the relative abundances of land cover classes, but assigns a weight to each land cover class according to the rank along a gradient of environmental quality. To clarify the ideas discussed, the method is illustrated with data from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In many cases very rapid socio-demographic dynamics have caused the creation of new landscapes whose changes have been studied by means of territorial analysis and modellistic approaches (Sui and Zeng 2001). It is also necessary to mention that landscape environmental quality often depends on the variety and dominance of land use classes (Ricotta et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases very rapid socio-demographic dynamics have caused the creation of new landscapes whose changes have been studied by means of territorial analysis and modellistic approaches (Sui and Zeng 2001). It is also necessary to mention that landscape environmental quality often depends on the variety and dominance of land use classes (Ricotta et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This relationship is relatively straightforward in the case of the habitat hectares approach and the hemeroby index, but it also holds in the case of ILC (and IVN) as it is shown in Appendix A. Ricotta et al (2003) provide further justification for the ILC approach, showing that ILC based landscape evaluation naturally conforms to the partial Lorenz ordering arising from the order of the naturalness categories-which can be seen as an important sanity criterion for any potential aggregation schemes. It can be shown that this partial Lorenz ordering is also preserved by all well defined NCIs (Appendix B).…”
Section: Aggregating Fine Scale Data For Low-level Policy Contextsmentioning
confidence: 80%
“…To show this, we first prove an even stronger lemma: that the formula of natural aggregation (NCI) equals to the Lebesgue integral of the function underlying the intrinsic Lorenz majorisation for landscapes suggested by Ricotta et al (2003). In other words, we show that ∀T ∈ T : NCI(T ) = [0,1]…”
Section: A≺ -B ⇒ Nci(a) ≤ Nci(b)mentioning
confidence: 98%
See 2 more Smart Citations